High-throughput integrated pretreatment strategies to convert high-solid loading microalgae into high-concentration biofuels. (November 2021) - Ha, Geon-Soo; Saha, Shouvik; Basak, Bikram; Kurade, Mayur B.; Kim, Gyeong-Uk; Ji, Min-Kyu; Ahn, Yongtae; Salama, El-Sayed; Woong Chang, Soon; Jeon, Byong-Hun
Highlights: Energy-saving microwave pretreatment required low specific energy (4.2 MJ/kg). Sequential fermentation completely disintegrated microalgal biomass. Unprecedented conversion efficiency (67%) was obtained from C. pitschmannii . Sustainable integrated pretreatment markedly enhanced high-titer biofuels production. Abstract: The commercial feasibility of energy-efficient conversion of highly concentrated microalgal suspensions to produce high-titer biofuels is a major bottleneck due to high energy consumption. Herein, high-titer biofuels (bioethanol, higher-alcohols, and biodiesel) were generated from carbohydrate-rich Chlamydomonas mexicana and lipid-rich Chlamydomonas pitschmannii biomass through energy-saving microwave pretreatment, successive fermentation, and transesterification. Microwave pretreatment needed low specific energy (4.2 MJ/kg) for 100 g/L of microalgal suspension. Proposed sustainable integrated pretreatments method achieved unprecedented total conversion efficiency (67%) and highest biomass utilization (87%) of C. pitschmannii (100 g/L) with high yields of bioethanol (0.48 g-ethanol/g-carbohydrates), higher-alcohols (0.44 g-higher-alcohols/g-proteins), and biodiesel (0.90 g-biodiesel/g-lipids). Transmission electron microscopy showed the changes in the microalgal cellular integrity before and after sequential fermentations. Energy-efficient integrated pretreatments enhanced the extraction efficiency and whole utilization of high-concentration microalgae to generate high-titer biofuels with minimum waste production.